Efficacy of platelet-rich plasma use as an adjunctive treatment in autologous osteochondral transplantation for patients with osteochondral lesions of the talus accompanied by chronic lateral ankle instability - Jie Xiao; Xiu Yang; Yun Zheng; Shun Lin; Xue-Song Han (Journal of Orthopaedic Surgery and Research)
Abstract Background Autologous osteochondral transplantation (AOT) combined with biological agents is an advanced technique for treating osteochondral lesions. Therefore, this study aimed to explore the effect of combining platelet-rich plasma (PRP) treatment with AOT on postoperative functional and magnetic resonance imaging (MRI) outcomes in patients with osteochondral lesions of the talus (OLTs) accompanied by chronic lateral ankle instability (CLAI). Methods This retrospective study had a minimum follow-up period of 1 year. Thiry-nine patients with CLAI who underwent AOT between 2019 and 2023 were included in this study. Of these, 21 and 18 received AOT combined with PRP treatment (AOT + PRP group) and AOT alone (AOT-alone group), respectively. Preoperative and postoperative follow-up assessments were performed using the visual analog scale (VAS), American Orthopedic Foot and Ankle Society (AOFAS), and foot and ankle ability measure-sport scale (FAAM-sport scale). The final follow-up MRI was evaluated using the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) 2.0 ankle scoring system. Results Both groups showed a significant reduction in VAS scores and significant improvements in AOFAS and FAAM-sport scale scores at the final follow-up compared with the preoperative values. No significant differences were observed in the final follow-up VAS, AOFAS, FAAM-sport scale, and MOCART 2.0 ankle scores between the groups. However, significant between-group differences were found at postoperative months 1 (P < 0.001) and 3 (P = 0.031) for VAS scores and at postoperative month 3 for FAAM-sport scale scores (P = 0.005). The AOT + PRP group showed significantly better final follow-up scores for the “surface of the repair tissue” on the MOCART 2.0 ankle score system than the AOT-alone group (P = 0.029). Conclusions PRP did not result in significantly superior outcomes when used as an adjunct to AOT compared to AOT alone in the setting of concomitant OLTs and CLAI.